Spermatozoa quality of Landrace Boar in Beltsville thawing solution diluent with various levels of moringa leaf extract - Wirona Adu; Thomas Hine; Aloysius Marawali; Wilmientje Marlene Nalley (Politeknik Negeri Jember, 2023)
This study aims to find the best level of sun-dried Moringa leaf extract (SDMLE) in Beltsville Thawing Solution (BTS) diluent to preserve the spermatozoa of Landrace boars. Semen from a two-year-old Landrace boar was collected using the massage method. Semen with spermatozoa motility ≥70% and spermatozoa abnormalities <20% was diluted with BTS (P0, control), BTS + 3% SDMLE (P1), BTS + 6% SDMLE (P2), BTS + 9% SDMLE (P3), and BTS + 12% SDMLE (P4). Storage of liquid semen using a cool box with a temperature of 15-20oC, while evaluating the quality of semen every 8 hours for spermatozoa motility, viability, abnormality, and longevity. The results showed that spermatozoa stored for 40 hours in BTS + 3% SDMLE (P1) diluent had higher quality (P<0.05) than the other four diluents, namely motility (54.00%), viability (61.16%), abnormality (3.62%), and longevity (45.77%). The results of this study concluded that 3% SDMLE added to BTS diluent was the best level for the preservation of spermatozoa in landrace boars.